2016
DOI: 10.1016/j.tet.2016.07.068
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, anti-proliferative activity, and toxicity of C4(C5) substituted N,N′-bis(arylmethyl)imidazolium salts

Abstract: The syntheses and characterization of C 4 and C 5 substituted N,N'bis(arylmethyl)imidazolium salts with hydrophilic or lipophilic substituents on the imidazole ring are reported. A structure-activity relationship study revealed that the lipophilicity of groups at the C 4 and C 5 positions plays a crucial role in modulating the efficacy against select non-small cell lung cancer cell lines tested. Compounds 11-17 were determined to be the most active against the panel of cell lines studied. Compounds 11 and 12 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…[5,6] The highly lipophilic N,N ′-bis(naphthylmethyl)imidazolium salt 1 exhibited high anti-proliferative activity against several NSCLC cell lines (Figure 2). It was shown that the in vitro anti-tumor activity of 1 was strongly correlated to the two naphthylmethyl substituents at the N 1 and N 3 positions of the imidazole ring.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] The highly lipophilic N,N ′-bis(naphthylmethyl)imidazolium salt 1 exhibited high anti-proliferative activity against several NSCLC cell lines (Figure 2). It was shown that the in vitro anti-tumor activity of 1 was strongly correlated to the two naphthylmethyl substituents at the N 1 and N 3 positions of the imidazole ring.…”
Section: Introductionmentioning
confidence: 99%
“…12 In particular, naphthylmethyl-substituted imidazolium salts, such as IS29 with a proton at the C 2 position, were shown to have high anti-proliferative effects against non-small cell lung cancer (NSCLC) (Figure 2). 1316 However, the clinical use of IS29 was limited by poor water solubility. The quinoline motif is structurally similar to a naphthalene substituent but has a nitrogen heteroatom to increase the hydrogen bonding capabilities and increase aqueous solubility, which has been shown previously by our group.…”
mentioning
confidence: 99%
“…The quinoline motif is structurally similar to a naphthalene substituent but has a nitrogen heteroatom to increase the hydrogen bonding capabilities and increase aqueous solubility, which has been shown previously by our group. 13,15,16 Also, the nitrogen atom could potentially be protonated to further increase the solubility if necessary. 17 Therefore, the historical quinoline motif and the novel, highly-active naphthylmethyl-based imidazolium salt could be combined to produce potent chemotherapeutics with high aqueous solubility.…”
mentioning
confidence: 99%
See 2 more Smart Citations